The Cambridge Encyclopedia of China (Cambridge Univ. Press, 1991)
The book is an absorbing and highly illustrated account of China's rich and colourful history and the life of its peeples. After death of Mao in 1976 and the re-emergence of Deng Xiaoping, a period of unprecedented modernization began in this most ancient and isolated of "superpower" nations. The reform programme of the early 1980s which changed the face of China's international relations also saw the emancipation of private initiative in sections of the economy; new, freer talents in literature and the arts and an upsurge in research into China's past and present. While change has been retarted and its scope narrowed it, the policy of reform and opening to the world still exists. This book has taken full account of recent developments in such areas as political history, the economy, administrative and economic geography, social organization, law, education, political philosophy and modern literature. All of which is illustrated by over 400 colour and black and white photographs and maps